Altered Macrophage Polarization Induces Experimental Pulmonary Hypertension and Is Observed in Patients With Pulmonary Arterial Hypertension. Issue 1 (January 2021) - Zawia, Amira; Arnold, Nadine D.; West, Laura; Pickworth, Josephine A.; Turton, Helena; Iremonger, James; Braithwaite, Adam T.; Cañedo, Jaime; Johnston, Simon A.; Thompson, A.A. Roger; Miller, Gaynor; Lawrie, Allan
Abstract : Objective: To determine whether global reduction of CD68 (cluster of differentiation) macrophages impacts the development of experimental pulmonary arterial hypertension (PAH) and whether this reduction affects the balance of pro- and anti-inflammatory macrophages within the lung. Additionally, to determine whether there is evidence of an altered macrophage polarization in patients with PAH. Approach and Results: Macrophage reduction was induced in mice via doxycycline-induced CD68-driven cytotoxic diphtheria toxin A chain expression (macrophage low [MacLow] mice). Chimeric mice were generated using bone marrow transplant. Mice were phenotyped for PAH by echocardiography and closed chest cardiac catheterization. Murine macrophage phenotyping was performed on lungs, bone marrow–derived macrophages, and alveolar macrophages using immunohistochemical and flow cytometry. Monocyte-derived macrophages were isolated from PAH patients and healthy volunteers and polarization capacity assessed morphologically and by flow cytometry. After 6 weeks of macrophage depletion, male but not female MacLow mice developed PAH. Chimeric mice demonstrated a requirement for both MacLow bone marrow and MacLow recipient mice to cause PAH. Immunohistochemical analysis of lung sections demonstrated imbalance in M1/M2 ratio in male MacLow mice only, suggesting that this imbalance may drive the PAH phenotype. M1/M2 imbalance was also seen in male MacLow bone marrow–derived macrophages and PAH patient monocyte-derived macrophages following stimulation with doxycycline and IL (interleukin)-4, respectively. Furthermore, MacLow-derived alveolar macrophages showed characteristic differences in terms of their polarization and expression of diphtheria toxin A chain following stimulation with doxycycline. Conclusions: These data further highlight a sex imbalance in PAH and further implicate immune cells into this paradigm. Targeting imbalance of macrophage population may offer a future therapeutic option. Abstract : Supplemental Digital Content is available in the text.